1999
DOI: 10.1177/002215549904700610
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Immunocytochemical Study of Na+, K+-ATPase in Rat Hepatocytes After STZ-induced Diabetes and Dietary Fish Oil Supplementation

Abstract: SUMMARYBecause diabetes causes alterations in hepatic membrane fatty acid content, these changes may affect the Na ϩ ,K ϩ -ATPase. In this study we documented the effects of streptozotocin (STZ)-induced diabetes on hepatic Na ϩ ,K ϩ -ATPase catalytic ␣ 1 -subunit and evaluated whether these changes could be normalized by fish oil supplementation. Two groups of diabetic rats received fish oil or olive oil supplementation. Both groups had a respective control group. We studied the localization of catalytic ␣ 1 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These effects of platelets on ox-LDL, as well as the activation of blood platelets by ox-LDL, contribute to the formation of the atherosclerotic lesion [24,25]. The interactions of blood platelets with atherogenic fractions of oxidised LDL can further contribute to the progression of atherogenesis through several mechanisms, including the augmented release of platelet-derived growth factor (PDGF) (a strong mitogenic and chemotactic agent) and β-thromboglobulin, enhanced synthesis of cholesterol esters in macrophages and monocytes, and increased uptake of oxidised LDL by macrophages [26]. It has been proposed that the binding of ox-LDL to the platelet surface leads to alterations in membrane fluidity, thus mediating the activating action of LDL on platelets.…”
Section: Low Density Lipoproteinsmentioning
confidence: 99%
“…These effects of platelets on ox-LDL, as well as the activation of blood platelets by ox-LDL, contribute to the formation of the atherosclerotic lesion [24,25]. The interactions of blood platelets with atherogenic fractions of oxidised LDL can further contribute to the progression of atherogenesis through several mechanisms, including the augmented release of platelet-derived growth factor (PDGF) (a strong mitogenic and chemotactic agent) and β-thromboglobulin, enhanced synthesis of cholesterol esters in macrophages and monocytes, and increased uptake of oxidised LDL by macrophages [26]. It has been proposed that the binding of ox-LDL to the platelet surface leads to alterations in membrane fluidity, thus mediating the activating action of LDL on platelets.…”
Section: Low Density Lipoproteinsmentioning
confidence: 99%
“…The sequence of events however appears to be more complicated than that suggested by Kowluru et al [4]. Caution is therefore advised when Na + /K + -ATPase activity is used as marker in studies of possible pharmaceuticals against secondary complications of diabetes [7,8,13,14,27,35,47] or in other experimental situations [17,18,33].…”
Section: Na + /K + -Atpase Activitymentioning
confidence: 99%
“…It has been reported that in diabetic humans as well as laboratory animals the activity of Na + /K + -ATPase in erythrocytes [2][3][4][5], blood vessels [6], peripheral nerves [7][8][9], brain [10], kidney [11][12][13], liver [14,15], pancreas [16], intestine [17], muscle [18,19], retina [20] and lens [21] is reduced by a factor of up to 7 [12].…”
Section: Introductionmentioning
confidence: 99%